2022
DOI: 10.1039/d1py01422f
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose coated nanocellulose to inhibit the infections by S. aureus

Abstract: Preventing bacterial infection by using antiadhesive compounds is one alternative to antibiotic treatment. Trehalose based polymers can serve as an antiadhesive agent that are selective to bacteria as trehalose is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Quantum mechanical calculations confirmed that each isomer maintained the clam shell conformation, important for the stabilizing properties of trehalose. 59 Stenzel and co-workers also exploited the high chain-end retention of RAFT polymerization to design and synthesize polymer–gold nanoparticle (AuNP) 69 or polymer-cellulose nanofiber (CNF) 70 constructs to inhibit microbial adhesion. In the first case, acetylated trehalose acrylate was prepared in three steps with a modest 7% overall yield.…”
Section: Polymerization Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantum mechanical calculations confirmed that each isomer maintained the clam shell conformation, important for the stabilizing properties of trehalose. 59 Stenzel and co-workers also exploited the high chain-end retention of RAFT polymerization to design and synthesize polymer–gold nanoparticle (AuNP) 69 or polymer-cellulose nanofiber (CNF) 70 constructs to inhibit microbial adhesion. In the first case, acetylated trehalose acrylate was prepared in three steps with a modest 7% overall yield.…”
Section: Polymerization Strategiesmentioning
confidence: 99%
“… Schematic illustration of (a) surface modification of CNFs with poly(trehalose acrylate) via Passerini reaction. Reproduced from ref ( 70 ) with permission from the Royal Society of Chemistry. (b) Synthesis of block copolymers via RAFT polymerization chain extension.…”
Section: Polymerization Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the use of trehalose glycopolymers as excipients providing enzyme stabilization under stress conditions 8,9 or allowing direct writing of protein patterns by electron-beam lithography, 10 as alternatives to PEGylation of therapeutic proteins, 11,12 inhibitors of amyloid fibrillogenesis, [13][14][15] and protein stabilizing and releasing smart (nano)hydrogels. [16][17][18] Trehalose incorporation has also been found to impart beneficial characteristics to macromolecular non-viral transfection agents such as pDNA, 19 cryopreservatives, 20 anti-adhesives to inhibit bacterial infections 21,22 and hydrogel matrices for 3D cell culture. 23,24 The activity of trehalose glycopolymers is usually investigated in the context of structural differences in these macromolecules, including the length of the linker structure between the trehalose moiety and the polymer chain, 14 the type of trehalose functionalization, 8 the position of functional group(s) on trehalose, 9 macromolecular topology, 25 molecular weight, 26 or the ratio of sugar to non-sugar moieties.…”
Section: Introductionmentioning
confidence: 99%